Cadmium(II) complexes of a hydrazone ligand: Synthesis, characterization, DNA binding, cyto- and genotoxicity studies. (1st October 2019) - Khandar, Ali Akbar; Azar, Zahra Mahmoudi; Eskandani, Morteza; Hubschle, Christian B.; van Smaalen, Sander; Shaabani, Behrouz; Omidi, Yadollah
Graphical abstract: DNA binding ability and cytotoxicity of two cadmium(II) complexes with a hydrazine Schiff base ligand compared with the free ligand were investigated. Thermodynamic parameters for the interaction between these compounds and DNA were calculated. Abstract: A new cadmium(II) complex, {[Cd(L)(NO2 )(CH3 CH2 OH)]·H2 O} n (1 ), based on HL Schiff base ligand (HL = 2-pyridinecarbaldehyde isonicotinoyl hydrazone) was synthesized and characterized by single crystal X-ray diffraction method. DNA binding interactions of the free HL ligand, complex1 and another cadmium complex with the same Schiff base ligand, [Cd(L)(CH3 COO)(OH2 )] n (2 ), were investigated using UV–Vis absorption, viscosity and fluorescence studies. These compounds could bind with the calf thymus-DNA via intercalation. The binding strength of these compounds to DNA was in the order of2  > 1  > HL with respect to their calculated K b values (150.0, 143.0 and 87.5 kM −1, respectively). The calculated thermodynamic parameters showed that the binding process of all these compounds to DNA is spontaneous (Δ G ° <0) and endothermic (Δ H ° >0) associated with increasing entropy (Δ S ° >0). Investigation of the cytotoxic activities of the two complexes against the human lung cancer cell line (A549) using MTT [3-(4, 5-dimethylthiazol-2-yl)-2, 5-diphenyltetrazoliumbromide] assay showed that their activity is almost in the region of cisplatin but much more than that of free HL ligand (IC50  = 138.27 ± 1.20, 46.31 ± 0.40, 32.01 ± 0.33 and 37.71 ± 0.20 μM for HL, 1, 2 and cisplatin, respectively). The genotoxicity studies of the complexes including DNA fragmentation and DAPI [4′, 6-diamidino-2-phenylindole] staining assays at IC50 (half maximal inhibitory) concentrations confirmed the induction of apoptosis and nuclear dysfunction by the complexes. Cell apoptosis induced by the complexes was detected through Annexin V/PI (propidium iodide) dual staining with flow cytometric analysis and the results indicated that the complex2 has higher apoptotic activity than1 .